ANALISIS TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA ADOPSI E-LEARNING PROGRAM STUDI TADRIS FISIKA UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG MENGGUNAKAN STRUCTURAL EQUATION MODELLING (SEM) - Dyah Ayu Malikatul Mukaromaha; Husni Cahyadi Kurniawan; Elok Fitriani Rafikasari (Media Bina Ilmiah, 2022)
E-learning is information technology and communication used in the learning process at UIN Sayyid Ali Rahmatullah Tulungagung. E-learning is used to replace face-to-face learning in full. The use of e-learning has not been maximally applied for various reasons, so an analysis of student perceptions of using e-learning is needed. The purpose of this research is to determine the level of acceptance of Tadris Physics students at UIN Sayyid Ali Rahmatullah Tulungagung on e-learning technology using the Technology Acceptance Model (TAM) structure as seen from Perceived Ease of use (PE) and Perceived Usefulness (PU). This research was conducted on 114 respondents who are students who use e-learning. Structural Equation Modelling (SEM) is used to data analysis. The result of this research shows that the variables that affect PE and PU are Training (T), Experience (E), and Facilitating Condition (FC).